The E3 ubiquitin ligase, NEDD4L (NEDD4-2) regulates bestrophin-1 (BEST1) by ubiquitin-dependent proteolysis - Park, Myeongki; Jung, Hyun-Gug; Kweon, Hae-Jin; Kim, Yeong-Eun; Park, Jae-Yong; Hwang, Eun Mi (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
The bestrophin family comprises well-known Ca2+-activated chloride channels (CaCC) that are expressed in a variety tissues including the brain, eye, gastrointestinal tract, and muscle tissues. Among the family members, bestrophin-1 (BEST1) is known to exist mainly in retinal pigment epithelium cells, but we recently reported that BEST1 mediates Ca2+-activated Cl- currents in hippocampal astrocytes. Despite its critical roles in physiological processes, including tonic gamma-aminobutyric acid release and glutamate transport, the mechanisms that regulate BEST1 are poorly understood. In this study, we identified NEDD4L (NEDD4-2), an E3 ubiquitin ligase, as a binding partner of BEST1. A series of deletion constructs revealed that the WW3-4 domains of NEDD4L were important for interaction with BEST1. We observed that BEST1 underwent ubiquitin-dependent proteolysis and found that the conserved lysine370 residue in the C-terminus of BEST1 was important for its ubiquitination. Finally, we demonstrated that NEDD4L inhibited whole cell currents mediated by BEST1 but not by the BEST1(K370R) mutant. Collectively, our data demonstrated that NEDD4L played a critical role in regulating the surface expression of BEST1 by promoting its internalization and degradation. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: CHANNELS; WW; RELEASE; FAMILY; DOMAIN; CELLS; GENE